Loss of integrin α1β1 ameliorates Kras-induced lung cancer - Macias-Perez, Ines (2008)
The collagen IV binding receptor integrin α1β1 has been shown to regulate lung cancer due to its pro-angiogenic properties, however it is unclear whether this receptor also plays a direct role in promoting primary lung tumors. To investigate this possibility, integrin α1-null mice were crossed with KrasLA2 mice which carry an oncogenic mutation of the Kras gene (G12D) and develop spontaneous primary tumors with features of non-small cell lung cancer. We provide evidence that KrasLA2/α1-null mice have a decreased incidence of primary lung tumors and longer survival compared to KrasLA2/α1 wild type controls. Tumors from KrasLA2/α1-null mice were also smaller; less vascularized and exhibited reduced cell proliferation and increased apoptosis, as determined by PCNA and TUNEL staining, respectively. Moreover, tumors from the KrasLA2/α1-null mice showed diminished ERK, but enhanced p38 MAPK activation. Primary lung tumor epithelial cells isolated from KrasLA2/α1-null mice showed a significant decrease in anchorage-independent colony formation, collagen-mediated cell proliferation, ERK activation, and, most importantly, tumorigenicity when injected into nude mice compared to KrasLA2/α1 wild type tumor cells. These results indicate that loss of the integrin α1 subunit decreases the incidence and growth of lung epithelial tumors initiated by oncogenic Kras, suggesting that both Kras and integrin α1β1 cooperate to drive the growth of non-small cell lung cancer in vivo.